Frequency of Bruxism among Mayofascial Temporomandibular Pain Disorder Patients: Frequency of Bruxism - Shahbaz, Ayesha; Mazher, Yamna; Shahid, Hassan; Asim, Hafiz Muhammad (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2024)
The connection between bruxism and temporomandibular disorders is complex and not yet well understood. Bruxism is a disorder marked by recurrent jaw movements that result in teeth clenching or grinding. It is frequently regarded as a significant risk factor for temporomandibular problems (TMD). Objective: To determine the frequency of bruxism among myofascial pain disorder in temporomandibular joint patients. Methods: A non-probability convenient sampling strategy was used to conduct a descriptive cross-sectional study with a sample size of 179 patients. Questionnaire was based upon the diagnostic criteria of American Academy of Sleep Medicine for bruxism and data were collected from Lahore Medical and Dental College and Ghurki Teaching Trust Hospital Lahore. Results: Out of the 179 patients 94 (52.5 %) reported symptoms of jaw joint noise and the frequency of bruxism in the participants was 106 (59.2 %). Conclusions: The study concluded that bruxism is more frequent in myofascial pain disorder in temporomandibular joint patients